Inclusive Innovation in Bean Value Chain Interventions: A Comparative Study of Gender Dynamics in Tanzania Malawi and Burundi - Lutomia, Cosmas Kweyu; Nchanji, Eileen Bogweh; Ketema, Dessalegn Molla; Ajambo, Susan; Puskur, Ranjitha; Kabuli, Hilda; Ndunguru, Agness; Ndabashinze, Blaise (CGIAR Initiative on Gender Equality, 2023)
As climate change relentlessly threatens the livelihoods of smallholder farmers regionally and globally, persistent gender disparities in the use of climate change adaptation strategies continuously impede achievement of resilience efforts. This study explored one research question: what specific strategies can be implemented to improve the inclusivity of bean value-chain innovations in Tanzania, Malawi and Burundi and enhance climate resilience? A cross-sectional survey that collected data from 656 respondents from three countries indicated that access to technologies and innovations varied across countries and genders, with women generally having lower access than men. The proportion of women using improved seed (48%) was significantly lower than men (67%) and irrigation technology usage was 40% for women and 48% for men. Commonly used sociotechnical innovation bundles were irrigation and conservation agriculture technologies, and innovations such as group membership, seed access models and information sharing. Limited access to information and training for women was a major gap in women’s ability to effectively adopt new technologies and practices. Implementation of inclusive innovation practices (participatory approaches, capacity building and context-specific solutions) demonstrated the potential to address gender disparities in adaptation to climate change. The results highlight need for gender-sensitive information dissemination and capacity-building initiatives to close gender gaps in climate change adaptation and resilience. Promoting inclusive innovation in agriculture and food systems and insights for policymakers, practitioners and researchers on designing and implementing genderresponsive interventions are recommended to foster inclusive innovations.